Levels of Health Care and Health Outcomes in Northeast India. Issue 2 (August 2019) - Hossain, Farhat
This article investigates basic parameters of health, namely health profile, health infrastructure, health expenditure and health care utilization in Northeast India and provides an analysis of regional disparities in health care sector. Health profile is represented through different health indicators like crude birth rate, infant mortality rate, total fertility rate and so on in the region. The status of Sub Centres, Primary Health Centres and Community Health Centres with their various facilities and manpower resources indicates better performance of most Northeastern states compared to the rest of India. However, in practice, the health centres in Northeast India do not fulfil some of the objectives and norms of Indian Public Health Standards. Further, the coefficient of variation shows the regional disparities is widening and worsening for health workforce in Northeast India. The geographic condition and inaccessible terrain of Northeast India seems to be a constraint, among others, in providing health infrastructure in the region.